Estimates of Surface and Subsurface Boundary Current Transport Around Australia. Issue 5 (17th May 2018) - Wijeratne, Sarath; Pattiaratchi, Charitha; Proctor, Roger
Abstract: A 15 year (2000–2014) simulation of the oceans around Australia, with the shelf‐scale model ozROMS, was used to estimate the mean, seasonal, and interannual variability of the surface and subsurface boundary currents and associated inflows. The simulation clarified some previous points of uncertainty and provided new information previously unknown and this is listed here. In the Indian Ocean, flow through the Timor Passage was linked to southeast Australia through the Holloway (HLC), Leeuwin (LC), South Australian (SAC), and Zeehan (ZC) Currents. The main inflows were from the Indonesian Throughflow and Eastern Gyral Current in the north whilst the central and southern branches of the South Indian Counter Current (SICC) provided major (>60%) inflows to the LC in the west. The HLC at North‐west Cape was at a maximum in April–May and its annual cycle accounted for 70% of the seasonal variance of LC, SAC, and ZC. In the Pacific Ocean, the northern branches of the South Equatorial Current were the main inputs to initiate the Hiri and East Australian (EAC) Currents flowing north and south, respectively, at ∼15°S. Inflow from the South Caledonia Jet to the EAC was ∼35%. The Flinders Current (FC) contributed to the Leeuwin Undercurrent (LU) directly as a northward flow and LU was enhanced from inflow from the subsurface southern SICC in the west (∼32–33°S). The majority of LU flowed westward offshore between 24 and 29°S while ∼25% continued northward to the northwest shelf. All Australian surface boundary currents systems were enhanced during the 2011–2013 La Niña. Key Points: Major inflows to the Leeuwin Current and Leeuwin Undercurrent are provided by the South Indian Counter Current The main inflow (65%) to the East Australian Current is through the northern branches of the South Equatorial Current All Australian boundary current transport was enhanced during the 2011–2013 La Niña